Developing a hippocampal neural prosthetic to facilitate human memory encoding and recall of stimulus features and categories - Roeder, Brent M.; She, Xiwei; Dakos, Alexander S.; Moore, Bryan; Wicks, Robert T.; Witcher, Mark R.; Couture, Daniel E.; Laxton, Adrian W.; Clary, Heidi Munger; Popli, Gautam; Liu, Charles; Lee, Brian; et al. (Frontiers in Computational Neuroscience, 2024)
Objective-Here, we demonstrate the first successful use during neural stimulation of static patterns for specific information content that were derived by models that were applied to a subject's own hippocampal spatiotemporal neural codes for memory. Here, we demonstrate the first successful use of static neural stimulation patterns for specific information content. These static patterns were derived by a model that was applied to a subject's own hippocampal spatiotemporal neural codes for memory.Approach-We constructed a new model of processes by which the hippocampus encodes specific memory items via spatiotemporal firing of neural ensembles that underlie the successful encoding of targeted content into short-term memory. A memory decoding model (MDM) of hippocampal CA3 and CA1 neural firing was computed which derives an activation a stimulation pattern offor CA1 and CA3 neurons to be applied during the encoding (sample) phase of a delayed match-to-sample (DMS) human short-term memory task.Main results-MDM electrical stimulation delivered to the CA1 and CA3 locations in the hippocampus during the sample phase of DMS trials facilitated memory of images from the DMS task during a delayed recognition (DR) task that also included control images that were not from the DMS task. Across all subjects, the stimulated trials exhibited significant changes in performance in 22.4% of patient and category combinations. Changes in performance were a combination of both spatiotemporal codes are able to modify memory performance in a content specific manner. This offers an alternate, and possibly complimentary, method of stimulation for use in a hippocampal prosthetic than that previously demonstrated.